ANALISIS PENGARUH SUHU DAN WAKTU PROSES PENGEPRESAN CUP SAMBAL MENGGUNAKAN ALUMINIUM FOIL LID - Kris Josua Pardede Kris; Robert Napitupulu; Shanty Dwi Krisnaningsih (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
Pressing chili cups greatly affects the quality and has an impact on the kemplang produced. The process of pressing the chili paste is still done manually, which is wrapped in plastic, then put into a container of chili kemplang. As a result, the kemplang could not last long. This study aims to determine the setting of temperature and time variables, as well as the percentage of the contribution of temperature and time variables that affect the pressing of chili cups using aluminum foil lid.  The research method used is referring to factorial Completely Randomized Design (CRD) with two variables. The first variable is temperature which consists of 3 levels, namely: 100 ° C, 150 ° C and 200 ° C. The second variable is the length of time holding which consists of 3 seconds, 4 seconds and 5 seconds. The treatment in this study was the result of a combination of variables from all levels of treatment, using the L9 Orthogonal Matrix (32). To avoid noise, each combination of variables was replicated 2 (two) times. The results showed that the best chili cup pressing variable setting was at a temperature of 150 ° C and a pressing time of 4 seconds, making the cups stick and close properly without any leakage. The largest percentage contribution from the influencing variable is temperature, amounting to 90.757%.